The Effects of Bureaucracy Internal Politics towards Citizen Satisfaction - Lanin, Dasman (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The contradiction between the point of view of organization-internal political games in bureaucracy and professional behaviour of bureaucrats has been a general issue of public service in Indonesian local government. Some researchers, as Mintzberg, have viewed organization-internal politics games in a bureaucracy as a certainty. Organization-internal politics has naturally existed in an organization with its positive impacts. The political games phenomena in a government bureaucracy could be a mechanism of dynamic changes of a status-quo. Meanwhile, some researchers have viewed that professional bureaucracy should be free from political party interests and cliques. In other words, they should be neutral and fair toward citizen in their services. The problem is whether this organization-internal politics can be a significant influence as a drive or determinant factor for citizen satisfaction with local government service. This article tries to reveal the influence of internal politics bureaucracy towards citizen satisfaction, in an effort to test the two variables in providing the basic needs of citizens. Quantitative approach is used in this study. The findings of this study indicate that the two variables were negatively correlated. Therefore, organization-internal politics could be an absolute predictor that has to be considered to citizen satisfaction with local government service as an outcome of service and democratic accountability of local public service provider.